1990
DOI: 10.1007/bf00155594
|View full text |Cite
|
Sign up to set email alerts
|

Genetic recombination in human melanoma and astrocytoma cell lines involves oncogenes and growth factor genes

Abstract: We describe here the chromosomal distribution of sister chromatid exchanges (SCEs) in four human tumor cell lines (two melanomas and two astrocytomas), and have mapped the sister chromatid recombination (SCR) sites. A higher incidence of SCR sites than expected on the basis of chromosome length occurred in chromosomes 2, 4, 5 and 15 in both the RPMI 5966 and MEL57 melanoma cell lines, and in chromosomes 1, 5, 13 and 15 of the IJKt and GUVW astrocytoma cell lines. A majority of the recombination sites occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The mechanism by which SCEs are produced in mammalian cells is yet to be fully determined, and its bio logical significance is unknown. However, SCEs can be induced by DNA-damaging properties of physical and chemical agents [74], Recent literature has revealed that spontaneous and induced SCEs frequently occur close to fragile sites on chromosomes indicating that fragility and SCE are variable cytogenetic manifestations of the same D N A structural alteration [75][76][77], SCEs might therefore represent variable expressions in inherent genomic insta bility within normal and transformed cell lines. For exam ple, elevated SCE levels have been found in mouse B16 melanoma cells and in cells from patients with Bloom's syndrome [78][79][80].…”
Section: Sce and Gene Amplificationmentioning
confidence: 99%
“…The mechanism by which SCEs are produced in mammalian cells is yet to be fully determined, and its bio logical significance is unknown. However, SCEs can be induced by DNA-damaging properties of physical and chemical agents [74], Recent literature has revealed that spontaneous and induced SCEs frequently occur close to fragile sites on chromosomes indicating that fragility and SCE are variable cytogenetic manifestations of the same D N A structural alteration [75][76][77], SCEs might therefore represent variable expressions in inherent genomic insta bility within normal and transformed cell lines. For exam ple, elevated SCE levels have been found in mouse B16 melanoma cells and in cells from patients with Bloom's syndrome [78][79][80].…”
Section: Sce and Gene Amplificationmentioning
confidence: 99%